PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PT. BANK MANDIRI (PERSERO) Tbk AREA MANADO - ANGGI WULAN LESTARI; Sofia A. P. Sambul (JURNAL ADMINISTRASI BISNIS, 2017)
The purpose of this study is to determine the effect of job satisfactionon organizational commitment in PT. Bank Mandiri (Persero) Tbk,Manado Area.This research is a quantitative research using simple regression analysisapproach. Data collection technique was done by distributing questionnairesfilled by 39 respondents. The results showed that job satisfaction has a significanteffect on organizational commitment of PT. Bank Mandiri (Persero) Tbk AreaManado. Based on the results of this study, companies should further increaseemployee satisfaction so that the organizational commitment of employees willalso increase.Keywords: Job Satisfaction, Organizational Commitment.